Perencanaan dan Pengawasan Pembangunan Gedung Kelas di Sekolah Dasar Islamic Global School (IGS) Kota Malang untuk Meningkatkan Mutu Pendidikan - taufik kurrahman; Arif Wahono; Lila Kurnia Wardani (Universitas Tribhuwana Tunggadewi Malang, 2021)
Elementary School of Islamic Global School (SD-IGS) Malang is one of the private schools located in Malang and established in 2010 in 10,000 m2. With the increasing number of students continues to grow in line with the achievement of accreditation rank B, the need for classroom infrastructure is very important. The condition of the existing class, there are still old class buildings with the condition of the building is worrying on safety. This devotion aims to provide detailed engineering design documents and budget plans for the cost of building classrooms as the basis for classroom construction. The method used is the science diffusion method. This community service produces a product of classroom planning documents and obtains the following conclusions; (1) there has been a plan of development activities in the form of classroom development planning documents; (2) the implementation of the construction of phase 1 classrooms that have development implementation documents that comply with the applicable regulatory standards. ABSTRAKSekolah Dasar Islamic Global School (SD-IGS) Malang adalah salah satu sekolah swasta yang berada di kota Malang. Berdiri pada tahun 2010 pada lahan seluas 10.000 m2. Seiring dengan pertambahan jumlah siswa yang terus meningkat seiring dengan tercapainya peringkat akreditasi B, maka kebutuhan akan sarana prasarana kelas sangat penting. Kondisi kelas yang ada, masih terdapat bangunan kelas yang sudah tua dengan kondisi bangunan yang mengkhawatirkan keamanannya. Tujuan dari pengabdian ini adalah untuk menyediakan dokumen gambar kerja dan rencana anggaran biaya pembangunan ruang kelas sebagai dasar untuk pelaksanaan pembangunan. Metode yang digunakan adalah metode difusi iptek. Pengabdian masyarakat ini menghasilkan sebuah produk dokumen perencanaan ruang kelas dan diperoleh kesimpulan sebagai berikut: (1) telah tersedianya dokumen perencanaan pembangunan ruang kelas; (2) telah terlaksananya pembangunan tahap 1 ruang kelas yang memiliki dokumen pelaksanaan pembangunan yang sesuai standar peraturan yang berlaku.